Characteristics and Lifestyle Related to Blood Sugar Levels in Type 2 Diabetes Mellitus Patients - Maria, Ida Leida (JURNAL INFO KESEHATAN, 2023)
Type 2 diabetes mellitus has been a prominent public health issue today. Globally, an estimated 462 million people are affected by type 2 diabetes, equivalent to 6.28% of the world's population. Globally, an estimated 462 million people are affected by type 2 diabetes, equivalent to 6.28% of the world's population. In Asia, especially Indonesia, the number of cases is expected to increase to 21.3 by 2030 in Indonesia. Type 2 diabetes is determined by blood sugar level, which affected by many factors including patients’ characteristics and lifestyle habits such as physical activity and diet. The Purpose of this research is to find the association between age, sex, education level, employment status, duration of disease, obesity, hypertension, diet, and physical activity with the blood glucose level of type 2 diabetic patients. This research used cross-sectional study design. The population is type 2 diabetes mellitus patients The population is type 2 diabetes mellitus patients who are spread over three areas of the city of Makassar, at the city center, suburban health center and coastal health center, total sample size of 273 patients The research was conducted sampling for 2 months via interview. The research instruments used were IPAQ and FFQ. The data analysis technique used is univariate and bivariate analysis, using chi-square. The results of this study indicate that found correlation between the variables. Lifestyle were found associated most with blood sugar level. Findings of the research found association between duration (p=0.003), obesity (p=0.000), hypertension (p=0.048), diet (p=0.000), and physical activity (p=0.000) with blood sugar levels. Meanwhile, age (p=0.461), gender (p=0.431), education level (p=0.357), working status (p=0.522), found not associated with blood sugar levels in patients with type 2 diabetes. The conclusion is duration Obesity, hypertension, diet, and physical activity were found associated with blood glucose level in type 2 diabetic patients. Patients with type 2 diabetes are expected to maintain blood sugar level by implementing healthy lifestyle. This includes regular physical activity and balanced diet.